Cultivating Innovation: The Mediating Role of Flexible Work Arrangements between Islamic Organizational Culture and Innovative Work Behavior in Philanthropic Institutions - Nurul Alvi Chindi Fadhilah; Solomon Mequanent Biwota (Perkumpulan Ahli Manajemen Dakwah Indonesia (PAMDI), 2025)
Purpose – This study examines the effect of Islamic organizational culture (IOC) on innovative work behaviour (IWB), with flexible work arrangements (FWA) serving as a mediator variable. Design/methodology/approach – A quantitative study methodology was utilized, employing questionnaires as the primary instrument for data collection, with data analyzed using SPSS version 26. The Sobel test was utilized to evaluate the mediating affect. The entire sample comprised 59 responders from six Islamic philanthropic institutions. Findings – The findings indicate that IOC exerts a positive and significant influence on FWA. Furthermore, there exists a notable positive and significant relationship between IOC and IWB. Additionally, FWA are shown to significantly enhance IWB. Nevertheless, the FWA does not serve as a mediator in the relationship between the IOC and the IWB. Research implications – The results affirm the significance of fostering Islamic principles that correspond with adaptable work policies to encourage innovative work behavior. Institutions ought to establish value-based frameworks (trust, fairness, integrity) and incorporate them into human resource practices, leadership, performance assessment, competency enhancement, and reward mechanisms. Originality/value – This study offers empirical data about the mediating function of FWA in the relationship between IOC and (IWB), utilising a sample of Islamic charitable institutions; it enhances the literature on value-based organizational behavior in a non-corporate context. Paper type - Research paper